2017
DOI: 10.32677/ijch.2017.v04.i01.002
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemia in neonate with perinatal asphyxia: Electrocardiographic, echocardiographic and enzymatic correlation

Abstract: Objective: The objective of this study is to evaluate the presence and severity of cardiac involvement in asphyxiated neonates and to established which clinical and laboratory parameters (electrocardiogram [ECG], echocardiography [ECHO], and cardiac enzyme) are reliable predictors of myocardial ischemia. Design: Nested case–control study. Setting: Neonatology unit of tertiary care institute. Materials and Methods: The study group consist of 90 term neonates who had APGAR score <7 at 5 min as cases and 90 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…ECG abnormalities were seen in almost 2-15% of cases in our study, which is lower than the study done by Rajakumar et al,(73.33%) and Agrwal et al,(76.77%). 8,9 Myocardial changes in birth asphyxia have similarly been described by Bhasin and Kohli, Kumar and Arasan, and; Merchant et al [10][11][12] Out of the total 150 cases, 72 died, and levels of CPKMB were elevated in 70 cases, which can be considered an early sensitive marker of mortality in severe birth asphyxia.…”
Section: Discussionsupporting
confidence: 54%
“…ECG abnormalities were seen in almost 2-15% of cases in our study, which is lower than the study done by Rajakumar et al,(73.33%) and Agrwal et al,(76.77%). 8,9 Myocardial changes in birth asphyxia have similarly been described by Bhasin and Kohli, Kumar and Arasan, and; Merchant et al [10][11][12] Out of the total 150 cases, 72 died, and levels of CPKMB were elevated in 70 cases, which can be considered an early sensitive marker of mortality in severe birth asphyxia.…”
Section: Discussionsupporting
confidence: 54%
“…In present study it was found that the mean CKMB levels were 133.9 IU/l which was comparable to the study done by Saira et al who had a mean CKMB level of 122.46 IU/l. 16 On contrary to this, Mandal et al reported CK-MB values as high as a 823.5 IU/l. 13 In present study, no baby was expired with normal CKMB levels.…”
Section: Discussionmentioning
confidence: 89%